Polymorphism 3435c> t of the ABCB1 gene (rs1045642) does not affect the mirtazapine efficiency and safety profile in patients with depressive disorders comorbid with alcohol use disorder - M. S. Zastrozhin; E. A. Grishina; K. A. Ryzhikova; V. Yu. Skryabin; S. G. Koporov; E. A. Bryun; D. A. Sychev (Бюллетень сибирской медицины)
Background. Mirtazapine is used to treat patients with depressive disorders. A large proportion of patients in this group do not adequately respond to mirtazapine therapy, while many develop undesirable drug reactions of type A. According to the previous studies, P-gp is involved in the biotransformation of mirtazapine, the activity of which is highly dependent on the polymorphism of the gene encoding it.Aim. The aim of our study was to study the effect of mirtazapine gene polymorphism on the efficacy and safety of mirtazapine therapy in patients with depressive disorders, comorbid with alcohol dependence.Materials and methods. The study included 119 male patients with depressive disorders, comorbid with alcohol dependence (age 38.7 ± 16.0 years). As a therapy, mirtazapine was used at a dose of 37.8 ± 13.8 mg / day. Evaluation of the effectiveness profile was carried out using psychometric scales. The safety profile was evaluated using the UKU Side-Effect Rating Scale. Genotyping was carried out by polymerase chain reaction in real time.Results. In the course of the study, results statistically significant in terms of evaluating efficacy and safety were not obtained (HAMD scores at the end of the course of therapy: (CC) 2.5 [2.0; 4.0], (CT) 2.0 [ 1.0; 3.0] and (TT) 2.0 [1.0; 3.0], p > 0.999; according to the UKU scale: (CC) 3.0 [2.8; 3.0], ( CT) 3.0 [3.0; 3.0] and (TT) 3.0 [3.0; 3.0], p > 0.999).Conclusion. The study of 119 patients with depressive disorders comorbid with alcohol dependence showed that 3435C> T polymorphism of the ABCB1 gene (rs1045642) does not affect the clinical efficacy and safety of mirtazapine.